(untitled) (Texas Journal of Engineering and Technology, 2022)
This article sheds light on the important aspects of the implementation of interdependence and integration of academic subjects in the teaching of subjects. The importance of interdisciplinary communication in effectively teaching the fundamentals of web design to students in general secondary schools is highlighted